I thought the minimum of P is 6 because from the equation P=2X^2 + (3-X)^2=3X^2-6X+9 by completing the square P=3(X-1)^2 + 6, hence the minimum value is 6. Even if we consider your answer that 0 is minimum then log x base 2 has to be zero > then x=1 and repeating the same argument we find that y=1 and unfortunately this contradicts the statement that xy=8 because if minimum P is 0 then xy has to be 1.

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewest\(P=2X^2+(3-X)^2\)) Minimum of P is at \(X=1\) or \((x,y)=(2,4)\) which is \(6\)

Log in to reply

I thought the minimum of P is 6 because from the equation P=2X^2 + (3-X)^2=3X^2-6X+9 by completing the square P=3(X-1)^2 + 6, hence the minimum value is 6. Even if we consider your answer that 0 is minimum then log x base 2 has to be zero > then x=1 and repeating the same argument we find that y=1 and unfortunately this contradicts the statement that xy=8 because if minimum P is 0 then xy has to be 1.

Log in to reply

You are right.

Log in to reply

from what

P=2X^2+(3−X)^2?Log in to reply

The questions asks us to express P in terms of X.

Log in to reply

2x^2, but i have question, from what(3−X)^2?Log in to reply

Log in to reply